Deformation failure mechanism and concrete-filled steel tubular support control technology of deep high-stress fractured roadway. (November 2022) - Chen, Bin; Zuo, Yujun; Zheng, Lulin; Zheng, Lujing; Lin, Jianyun; Pan, Chao; Sun, Wenjibin
Highlights: Deformation and failure mechanism analysis of deep high-stress fractured roadway. Establishment of the surrounding rock-support coupling model. Mechanical response characteristics of CFST support under dynamic disturbance. Supporting effect evaluation of CFST support by microseismic monitoring. Field test of CFST support control technology. Abstract: To address the problem of deep high-stress fractured roadway support, a water sump in a 30 m middle section of the Jinfeng Gold Deposit was taken as an engineering background. The deformation failure characteristics of the roadway under the original support scheme were analysed, and the deformation failure mechanism was assessed by combining the geological conditions, geological mechanism, and original support scheme. Numerical experiments were performed to analyse the bearing performance of concrete-filled steel tubular (CFST) supports and U-shaped steel supports under dynamic and static loads. The experiments showed that with the same lateral pressure coefficient, the stress of CFST support is approximately half of that of U-shaped steel support, and the deformation is decreased by 30–40 %. Meanwhile, under the same charge weight, the stress and deformation of the CFST support are always lower than those of the U-shaped steel support. In engineering practice, the support scheme based on circular-section CFST supports showed no obvious deformation after sixty days of use, and the surrounding rock produced few microseismic events and no significant expansion or concentration of microfractures. The stability of the roadway surrounding rock was efficiently maintained, which offers guiding implications for similar projects.